Penile Agenesis - I. J. Gupta; Ramesh Chandra (Indian Journal of Plastic Surgery, 1977)
This rare congenital znomaly had been reported in only 37 cases The condition is a result of incomplete development of the genital tubercle. Other urogenital anomaly should be investigated thoroughly. The sex assignment should be done by taking into consideration the psychological aspect, harmonal and chromosomal study. The surgical interference should be done in those cases who survive infancy and childhood.